Kemampuan Penalaran Matematis Siswa melalui Pendekatan Realistic Mathematics Education Di SMP Negeri 5 Padangsidimpan - Almira Amir; Nora Nora (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This study aims to improve students' mathematical reasoning on the subject matter of cubes and blocks through the Realistic Mathematics Education (RME) approach. This is motivated by the low mathematical reasoning of students at the time of learning.This research is a type of Classroom Action Research using Kurt Lewin's model which consists of two cycles, each cycle consists of four steps, namely: planning, action, observation, and reflection. Data collection instruments used in the form of tests and observations. This research was conducted in class VIII3 of SMP Negeri 5 Padangsidimpuan in April 2019. The results of this study indicate that the action hypothesis is accepted. Mathematical reasoning ability of students showed an increase in the pre-cycle of students' mathematical reasoning completeness was 21.74% (5 people), in the first cycle of meetings 1 and 2 students' completeness was 47.83% (11 people) and 60.87% (14 people). In the second cycle of meetings 1 and 2, the students' completeness was 73.91% (17 people) and 86.95% (20 people). The percentage of mathematical reasoning completeness of the students above has reached 80% of the number of students, so this research is said to have been successful. For further researchers, it is hoped that they can use the results of this study as a study for conducting further research on the application of the Realistic Mathematics Education (RME) approach to wider materials on cubes and blocks.